2019
DOI: 10.3390/antiox8080293
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Value, Chemical Composition and Cytotoxic Properties of Common Purslane (Portulaca oleracea L.) in Relation to Harvesting Stage and Plant Part

Abstract: Purslane (Portulaca oleraceae L.) is a widespread weed, which is highly appreciated for its high nutritional value with particular reference to the content in omega-3 fatty acids. In the present study, the nutritional value and chemical composition of purslane plants in relation to plant part and harvesting stage were evaluated. Plants were harvested at three growth stages (29, 43 and 52 days after sowing (DAS)), while the edible aerial parts were separated into stems and leaves. Leaves contained higher amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 38 publications
5
51
3
3
Order By: Relevance
“…In contrast to our study, Nemzer et al [59] reported a higher total and individual organic acids content in cultivated purslane plants compared to wild ones, although different genotypes were tested in both cases which may partially justify this difference [60]. According to the literature, organic acids composition shows a great variability among wild edible species, depending on the edible part and the growing conditions [20,[60][61][62][63]. Special focus is given on oxalic acid content which is undesirable when consumed in high amounts (daily consumption higher than 5 g for adults; [31]), since it reduces Ca availability and induces the formation of kidney stones [64,65].…”
Section: Organic Acids Compositioncontrasting
confidence: 93%
See 2 more Smart Citations
“…In contrast to our study, Nemzer et al [59] reported a higher total and individual organic acids content in cultivated purslane plants compared to wild ones, although different genotypes were tested in both cases which may partially justify this difference [60]. According to the literature, organic acids composition shows a great variability among wild edible species, depending on the edible part and the growing conditions [20,[60][61][62][63]. Special focus is given on oxalic acid content which is undesirable when consumed in high amounts (daily consumption higher than 5 g for adults; [31]), since it reduces Ca availability and induces the formation of kidney stones [64,65].…”
Section: Organic Acids Compositioncontrasting
confidence: 93%
“…Despite the higher oxalic acid content of cultivated C. raphanina spp. mixta plants observed in our study, the detected amounts are lower than those reported on a fresh weight basis in other wild (e.g., Chenopodium album [69], Sonchus oleraceus [61,70], Amaranthus viridis [71], Silybum marianum and Beta maritima [61], and purslane [60,62]) or cultivated species (e.g., spinach [72]) which are considered as rich sources of this anti-nutritional factor. Therefore, based on the set safe limit high amounts of C. raphanina spp.…”
Section: Organic Acids Compositioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the broader Mediterranean region is characterized by small-scale farming which is the back-bone of the farming sector and of rural economies and is under increasing pressure due to land allocation for non-agricultural uses and to the ongoing climate change [2][3][4]. The ability of wild species to resist or tolerate stressful conditions suggests they could be used as alternative farming options in soils and climates where conventional species are difficult or impractical to be grown; for the same reason, these species can become an option for small-scale farming allowing the farmers to be competitive within the rapidly changing global market and market needs for novel foods [5][6][7][8][9][10]. Until recently, many reports have highlighted the importance of growing conditions and cultivation practices for producing wild edible greens, focusing on the domestication of these species, their incorporation in sustainable cultivation systems and the rational use of natural resources [2,[11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the phenolic profile of the plant in each stage was also described by the authors. Petropoulos et al [9] performed the nutritional and chemical composition evaluation of different parts of Portulaca oleracea L., namely stems and leaves, harvested in three growth stages. Additionally, the cytotoxicity of these samples was also assessed.…”
mentioning
confidence: 99%